Layer-by-layer assembled black phosphorus/chitosan composite coating for multi-functional PEEK bone scaffold. (November 2022) - He, Miaomiao; Zhu, Ce; Sun, Dan; Liu, Zheng; Du, Meixuan; Huang, Yong; Huang, Leizhen; Wang, Juehan; Liu, Limin; Li, Yubao; Song, Yueming; Feng, Ganjun; et al.
Abstract: A layer-by-layer (LBL) assembled black phosphorus nanosheets/chitosan (BP-NS/CS) multi-functional composite coating has been developed and deposited onto 3D printed PEEK bone scaffold to enable its application for osteosarcoma management and bone repair. The graded 3D PEEK scaffold provides the ideal mechanical properties and architecture that match that of the natural bone. The CS within the composite coating can effectively protect BP-NS from fast degradation and allows sustained release of PO4 3− for accelerated bone regeneration. In addition, the composite coating consisting of BP (as photothermal agents) and drug-laden CS can enable bone tumor ablation through multi-modal therapy combining on-demand laser induced heating and pH sensitive cancer drug release. The BP-NS also release reactive oxygen species that effectively eradicate E. coli and S. aureus, hence help tackle the potential post-operation infection. The bone regeneration performance of the scaffold has been thoroughly assessed. Results show that the composite coating has endowed the scaffold with enhanced biocompatibility and osteogenesis-associated gene expression. The multi-functionality of our coated scaffold including tumor inhibition, bacteria eradication and bone regeneration has also been demonstrated in animal studies. The promising results suggest the strong potential of our new scaffold system in challenging applications such as osteosarcoma treatment and bone repair. Highlights: A composite coating of BP-NS and chitosan was deposited onto 3D PEEK scaffold through a layer-by-layer assembly approach. The presence of chitosan effectively protects BP-NS from fast degradation. BP-NS's photothermal conversion was combined with cancer drugs released from chitosan for chemo-photothermal therapy. The ROS released from BP-NS has strong bacteria eradication effect. The composite coating significantly boosts the implant's bone regeneration ability due to release of PO4 3− from the BP-NS.